Mineralogical and petrophysical research of pyroclastic rock of volcano Eyjafjallajokull (Iceland) - V Yu Abramov; G N Kolosova; T V Kondratieva (RUDN Journal of Engineering Research, 2011)
Take a mineralogical and petrophysical research of pyroclastic rock of volcano Eyjafjallajökull. Test a mineral composition and petrophysical properties of pyroclastic rock.